Quantifying Insect Cell Nutrition for Use in Cellular Agriculture. - Soule-Albridge, Erin. (Tufts University. Tisch Library., 2022)
Cellular agriculture is defined as creating and producing agricultural products such as meat by using cell culture instead of traditional agriculture involving animals. Meat produced via cellular agriculture is called cultured meat which is created by first isolating cells from a donor animal. These initial cells are then multiplied and grown in specific conditions to create meat relevant tissues. However, there are many challenges to creating a cost effective, scalable, and nutritious final product using mammalian cells such as bovine. There is a different cell type which can circumvent these issues, insect cells. Insect cells are grown at lower temperatures and without CO2 regulation similar to ambient conditions, have a slower buildup of toxic byproducts, do not require additional growth factors and in fact produce their own. These factors allow for cost reduction and easy scalability in comparison to mammalian cells. One aspect still to be quantified with primary insect cells for use in cellular agriculture products is nutritional value. Insects are known to be more nutritious than steaks and other common meat cuts and it is assumed that insect cells follow this trend and are more nutritious than mammalian cells. Previous research into representative cell lines of insect and mammalian cells has shown insect cells are more dense in protein, zinc, and iron. Now, the nutritional testing (protein, zinc, and iron) of a primary insect cell species compared to primary bovine satellite cells will be explored. While many more nutritional aspects are still to be quantified, insect cells show promise in the field of cellular agriculture to create meat to supplement the growing market demand.; 3-minute talk presented at the Tufts Graduate Student Council's 27th Graduate Student Research Symposium, April 20, 2022, 2nd place winner.